Annali Online di Ferrara [...] Lettere - Università di Ferrara, Dipartimento di Studi Umanistici (Univ. degli Studi di Ferrara, 2006)
Devoted to research and scholarship in nnn and nnn.
Keywords: Social Sciences : Periodicals; Humanities : Periodicals; Italy